Centre/Fold : newsletter of the Toronto Centre for Lesbian and Gay Studies. (Toronto : Toronto Centre for Lesbian and Gay Studies, 1995)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : 2 Bloor Street West, Toronto ON M4W 3E2
Engels
Periodiek